2010
DOI: 10.1063/1.3497079
|View full text |Cite
|
Sign up to set email alerts
|

Composition and growth direction control of epitaxial vapor-liquid-solid-grown SiGe nanowires

Abstract: The composition and growth direction of epitaxial SiGe alloy nanowires (NWs) grown via the Au-catalyzed vapor-liquid-solid technique can be controlled by varying growth conditions. These alloy NWs can adopt either Si-like or Ge-like characteristics. Si-like growth is characterized by Au-coated ⟨111⟩-oriented NWs for low pressure growth and Au-free ⟨112⟩-oriented NWs for higher pressure growth. Ge-like NWs always follow ⟨111⟩ and grow with Au-free sidewalls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…As mentioned above, the formation of quaternary pseudobinary solid‐solution nanowires can be regarded as a random process of simultaneous doping (or substitution) with anions and cations. Compared to binary or ternary solid‐solution nanostructures, quaternary solid‐solutions are composed of two different binary compounds and consequently consist of four different elements. The increased number of constituting elements undoubtedly complicates the homogeneous solidification process and the realization of phase purity, making the formation of a single‐phase solid‐solution more challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the formation of quaternary pseudobinary solid‐solution nanowires can be regarded as a random process of simultaneous doping (or substitution) with anions and cations. Compared to binary or ternary solid‐solution nanostructures, quaternary solid‐solutions are composed of two different binary compounds and consequently consist of four different elements. The increased number of constituting elements undoubtedly complicates the homogeneous solidification process and the realization of phase purity, making the formation of a single‐phase solid‐solution more challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the tuning of properties of semiconductors have demonstrated that the alloying or solidification of foreign elements (or compound) into the host lattices can lead to significant changes in energy band‐gap, electrical transport, lattice constant, and luminescence properties, respectively . Up to date, successful property tuning has been reported for numerous binary and ternary solid‐solution systems such as SiGe, ZnCdSe, ZnSSe, PbSeTe, CdZnTe, InGaN, AlGaN, InGaAs, and GaAsP …”
Section: Introductionmentioning
confidence: 99%
“…These growth modes exhibit a structure that is different, but again counterintuitive, in that the {111}-faceted liquid-solid interface is now tilted at an angle to the growth direction [1,4,5,7]. The growth direction can be controlled experimentally by the growth conditions [5,8]. This is understood only qualitatively -the surface incorporates Au and/or H or other vapor-derived species, depending on temperature and source-gas pressure, and these in turn affect facet energies [6,8,9,10].…”
mentioning
confidence: 99%
“…Motivated by the previous studies that Si 1Àx Ge x NWs grow preferentially along the (1 1 1) direction [20,21], we adopted (1 1 1)-oriented SiNW with a diameter of 0.89 nm. The dangling bonds of surface Si atoms are saturated with hydrogen atoms, and the initial lattice constant of a = 0.5470 nm is obtained the same as that of bulk Si, as shown in Fig.…”
Section: Geometry and Structural Detailsmentioning
confidence: 99%